EFEKTIVITAS BAHAN AJAR BAHASA INDONESIA BERBASIS DIGITAL LIBRARY UNTUK MENINGKATKAN KEMAMPUAN MEMBACA INTENSIF SISWA KELAS VI SD - Lestari, Heni Suci (INOPENDAS: Jurnal Ilmiah Kependidikan, 2023)
This study aims to find out the effectiveness of teaching materials Indonesian based on digital libraries to improve the intensive reading skills of students of grade VI SD N 3 Krasak Pecangaan Jepara 2021/2022 with 35 students. Also to find out the supporting factors and inhibitions of the application of digital library-based teaching materials.This type of research is qualitative descriptive. The result of this study is the effectiveness of the application of digital library-based teaching materials seen based on the average percentage of student responses to the use of teaching materials by 88.70%. Furthermore, 92% of students obtained the completeness of the learning outcome test. Supporting factors in the application of digital library-based teaching materials are obtained from observations during the learning process, are: availability of LCD Projectors in classrooms; 100% of students have gadgets; student skills operating gadgets. An inhibitory factor in the application of teaching materials is SD N 3 Krasak wifi that does not reach class VI rooms and materials in digital libraries that are still limited.